2018
DOI: 10.1016/j.otsr.2018.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Posterior pelvic ring fractures: Intraoperative 3D-CT guided navigation for accurate positioning of sacro-iliac screws

Abstract: IV, Retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…Using 3D fluoroscopic navigation when performing pelvic surgery is reported to be useful in planning screw position. The above disadvantages could be reduced with 2D-or 3Dfluoroscopic navigation, but the malposition rate of screw fixation for pelvic fractures ranges from 0% to 31%, demonstrating that there's still certain room to improve the technology [27][28][29] . Additionally, too much radiation exposure to patients and surgeons will also cause great harm to their bodies.…”
Section: Clinical and Radiological Results With Robot-aided Surgerymentioning
confidence: 99%
“…Using 3D fluoroscopic navigation when performing pelvic surgery is reported to be useful in planning screw position. The above disadvantages could be reduced with 2D-or 3Dfluoroscopic navigation, but the malposition rate of screw fixation for pelvic fractures ranges from 0% to 31%, demonstrating that there's still certain room to improve the technology [27][28][29] . Additionally, too much radiation exposure to patients and surgeons will also cause great harm to their bodies.…”
Section: Clinical and Radiological Results With Robot-aided Surgerymentioning
confidence: 99%
“…A retrospective, single-center cohort study on 102 traumatic patients was reported by Pishnamaz et al [ 33 ]. Misplacement in conventional placed screws is reported to be between 8.8–12.4% [ 4 , 33 , 34 ] in conventionally techniques and 3.6–4.9 % using 3D navigation [ 4 , 35 ]. We found correct screw placement in 91.23%, whereas minor screw displacement (<3.6 mm) occurred in 4.5% and major displacement was seen in 3.08%.…”
Section: Discussionmentioning
confidence: 99%
“…Most reports on screw misplacement and safety report on traumatic pelvic fractures [ 2 , 4 , 33 , 34 , 35 , 36 ]. The present study does not differentiate between traumatic and fragility fractures in this specific context.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the time required to place each screw and the radiation exposure times in the guide apparatus group was significantly better than in the free-hand group, and no complications were noted at the final follow-up. Although much time was spent in finding the exiting point, the duration of the operation and the number of fluoroscopy exposures were significantly reduced, and there are no expensive surgical instruments required because the manufacture of the guide apparatus is simpler and cheaper than a robot, CT machine, or 3D navigation [24]. Ultimately, surgeons who are adept at inserting iliosacral and transiliac-transsacral screws can master this technique with a small learning curve.…”
Section: Discussionmentioning
confidence: 99%